1998
DOI: 10.1111/j.1467-8624.1998.tb06153.x
|View full text |Cite
|
Sign up to set email alerts
|

The Medium Can Obscure the Message: Young Children's Understanding of Video

Abstract: In the first few years of life, children acquire a great deal of general information through symbolic media, including television. Here we explored whether very young children would use information presented via video to solve a retrieval problem. The children watched on a monitor as a toy was hidden in the room next door. A group of 2%-year-olds was very successful at finding the hidden toy based on the televised hiding event, but a group of 2-year-olds was not. Substantially better performance was achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
256
3
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(285 citation statements)
references
References 40 publications
19
256
3
7
Order By: Relevance
“…This study also agrees with findings that children whose parents determine the time and the kind of television programme watch less television [7,8].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…This study also agrees with findings that children whose parents determine the time and the kind of television programme watch less television [7,8].…”
Section: Methodssupporting
confidence: 91%
“…Researchers have found several characteristics which influence television watching habits of children [1,2,[4][5][6][7][8]. In Greece there are no studies concerning television watching during hospitalization and this fact was the motivation to conduct the present survey.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research comparing live versus comparable screen-based situations has found lower levels of learning from television for children under approximately 30 months for a variety of tasks (e.g., Barr and Hayne 1999;Hayne et al 2003;Kuhl et al 2003;Troseth and DeLoache 1998), a pattern referred to as the video deficit (Anderson and Pempek 2005), or, more recently, the transfer deficit (Barr 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Perseverative responding, defined as a tendency to repeat a previous response, has been demonstrated in children's performance in a variety of contexts, including symbolic comprehension (DeLoache, 1995a;DeLoache, Pierroutsakos, Uttal, Rosengren, & Gottlieb, 1998), A-not-B tasks (Bjork & Cummings, 1984;Cummings & Bjork, 1981;Diamond, 1985;Piaget, 1936Piaget, /1954, spatial recognition (Bremner, 1978;Bremner & Bryant, 1977), and cognitive inflexibility (Zelazo & Frye, 1997;Zelazo, 2002;Suddendorf, 2003;Troseth & DeLoache, 1998). 1 Given the frequent nature of such responses, it is of interest to further investigate the source of this perseverative responding in symbolic tasks.…”
Section: Introductionmentioning
confidence: 99%